Liver blood chemistry profile of the American crocodile (Crocodylus acutus) raised in captivity - Zender A., Jhonathan (2016)
The liver blood chemical profile of the American crocodile (Crocodylus acutus) raised in captivity in the northern region of Peru was determined. Sixty crocodiles were sampled from a population of 255 animals belonging to the Zoocriadero del Centro de Acuicultura La Tuna Carranza, part of the National Fisheries Development Fund (FONDEPES) located in the region of Tumbes, Peru. The animals were classified as young (n=24), subadults (n=27) and adults (n=9). A blood sample (6 ml) was taken from each animal by puncturing the post-occipital venous sinus while animals were under physical restraint. Serum was separated by centrifugation and concentration of each enzyme was measured by spectrophotometry. Variables studied were alanine aminotransferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (ALP), total bilirubin, direct bilirubin, indirect bilirubin, total protein and albumin. Statistical difference (p<0.05) was found between age groups in ALT, FA, direct bilirubin, and total protein. All values with the exception of albumin showed high biological differences with those reported by the International Species Information System.